INOVASI BAHAN AJAR DIGITAL DALAM PENDIDIKAN ANAK DI ERA SOCIETY 5.0 - Ameliana Balya sakti (LPPM IAD Probolinggo, 2026)
The rapid advancement of digital technology has transformed contemporary educational practices, leading to the emergence of Society 5.0, which emphasizes human-centered, personalized, and technology-integrated learning. This study examines current trends and challenges in the development of digital instructional materials within the context of Society 5.0. Employing a qualitative library research approach, this study systematically reviews and analyzes 35 scholarly publications published between 2018 and 2023 using qualitative content analysis. The findings reveal that adaptive learning systems, gamification, mobile learning, and immersive technologies such as augmented and virtual reality constitute the dominant trends in digital instructional innovation. However, significant challenges persist, including limited pedagogical competence, unequal digital infrastructure, insufficient digital literacy among educators, and weak institutional support. Theoretically, this study extends the TPACK framework by integrating ethical and humanistic dimensions aligned with Society 5.0 principles. Practically, it offers strategic recommendations for educators and policymakers to design sustainable, inclusive, and pedagogically meaningful digital instructional materials.